Germanic metamorphosis of Don Quixote - Esteve Montenegro, María Luisa (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This work deals with the Cervantine presence, concretly with Don Quixote, in the German literature of the last third of the XVIIIth century and with how Wieland, inspired by the novel of Cervantes, realizes more than an imitation a parody of Don Quixote achieving a new form of ficcional transformation.